Peluang Pengembangan Voluntourism Berbasis Masyarakat di Hutan Mangrove Batu Lumbang, Suwung, Pemogan, Denpasar - Tyas, Septianing; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA; Vol 8 No 2 (2020): VOL 8, NO 2 (2020): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2020.v08.i02.p24, 2020)
The Mangrove Batu lumbang as conservation areas where live so many variety of flora and also has so beautiful view. Although the mangrove has not yet defined it as a tourist attraction, there are few tourist visitors. Assets or potential have been particularly supportive to develop as alternative tourism but there are some issues about garbage and waste. Voluntourism has become one of the best types of alternative tourism to develop. Voluntourism or volunteer tourism is a form of tourism where tourists use leisure time as volunteers and donators on conservation projects in an attraction. The purpose of this study is to identify the chances of voluntourism development in the mangrove forest Batu Lumbang based communities to help the ecosystem and grow the communities also give a new experience for tourist. The study used qualitative descriptive methods. The result of this study is the mangrove forest Batu Lumbang fillup some of the criteria of voluntourism activity. The criteria of the study based on the criteria of the global tourism business industries. The limits of this research are the time to finding data due to a covid-19 outbreak.   Keyword : voluntourism; Hutan Mangrove Batu Lumbang; Responsible Tourism